2022
DOI: 10.1007/s00420-022-01900-5
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to particles and biomarkers of cardiovascular disease—during work and after vacation

Abstract: Objective Ambient particle matter is a risk factor for cardiovascular disease (CVD). However, little is known about associations between particles in occupational settings and risk of CVD. We investigated associations between occupational dust exposure and biomarkers of CVD, and potential recovery effects after vacation. Methods Personal dust exposure measurements (respirable silica, respirable dust < 4 µm, and particles of 0.1–10 µm (PM 0.1–10) were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…To our knowledge, our results are the first to investigate and showcase an association between WTC-related exposure and increases in glucose and total cholesterol levels. Previous literature supports an association between non-WTC occupational dust exposure and increased risk of diabetes ( 30 ) and diverse cardiovascular disease risk markers ( 31 ). Several longitudinal studies have shown associations between WTC-related exposures and heart disease ( 32 ), stroke ( 33 ), and overall cardiovascular disease risk ( 34 ).…”
Section: Discussionmentioning
confidence: 83%
“…To our knowledge, our results are the first to investigate and showcase an association between WTC-related exposure and increases in glucose and total cholesterol levels. Previous literature supports an association between non-WTC occupational dust exposure and increased risk of diabetes ( 30 ) and diverse cardiovascular disease risk markers ( 31 ). Several longitudinal studies have shown associations between WTC-related exposures and heart disease ( 32 ), stroke ( 33 ), and overall cardiovascular disease risk ( 34 ).…”
Section: Discussionmentioning
confidence: 83%
“…The study group consisted of construction workers (N=65) with exposure to particulate matter and RCS who were recruited 2018/2019 from 20 companies in the Stockholm County, as previously described ( 9 ). The inclusion criteria were that the participants should be males, non-smokers for the last six months and have worked in the construction industry for at least six months.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the questionnaire covered former and current work including years in profession (years), exposure to noise, exposure to other particles during work (ie, diesel fumes, welding, dust other than RCS) or from hobbies. Biological samples were collected twice for each participant: during work (ie, in the morning before participants started the working day, and the same day as the exposure measurements) and after vacation (but before returning to work) as previously described ( 9 ). During the measurements after vacation, participants completed another short questionnaire about vacation activities involving exposure to RCS, health status, and tobacco use.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations